COMPARATIVE ASPECTS OF CONSTITUTIONAL BASES FOR FREEDOM OF ECONOMIC ACTIVITY - Juškevičiūtė-Vilienė, Agnė (Teisė, 2015)
Using comparative method, this article analyses constitutional basics of freedom of economic activity provided in the Constitutions of Lithuania, Poland, and Germany and their constitutional jurisprudence. The article is divided into three sections that respectively analyse the content of freedom of economic activity, its subjects, and the guaranteed limit of freedom of economic activity. The novelty of the article is demonstrated by the analysis of constitutional jurisprudence on freedom of economic activity in Lithuania, Poland, and Germany. The research showed that some countries recognize the freedom of economic activity as a constitutional subject right, and the others – as the economic basics of state that create the constitutional principle. Legal status of economic activity subjects in Germany and Poland are differentiated according to their form of property. Meanwhile, all Constitutional Courts of analysed countries distinguish the same special limitation conditions for economic activity: these limits should be prescribed by legislation and be based on public interest. The article provides the analysis of constitutional freedom of individual economic activity and initiative, which provides with assumption that this freedom will become simpler for both institutions that create the state economic policy and subjects that implement this freedom.